Registro de imagens aplicado à manipulação industrial robotizada - Camargo, Gustavo de (My University, 2022)
Robot referencing in industrial object manipulation applications is typically based on pattern recognition techniques. However, this type of solution is stronghighly dependent on training, is computationally expensive, and is generally not susceptible to a theoretical performance analysis. In this work, the application of image registration algorithms is proposed to estimate the position and orientation of the objects to be manipulated. Therefore, we propose the use of a method based on Phase Correlation, in order to segment the object of interest and, simultaneously, estimate the parameters of interest. As one of the main contributions, considerations about the registration of images using Phase Correlation are presented, highlighting limitations that apparently went unnoticed by the scientific community in the last 25 years. Based on these considerations, under test conditions of interest to the application and assuming the mean absolute error as a figure of merit, the proposed method improves the performance of estimation of rotational movements by more than 1000% in relation to the way in which the Phase Correlation method is presented in the literature. [resumo fornecido pelo autor]
O referenciamento de robôs em aplicações industriais de manipulação de objetos é tipicamente baseado em técnicas de reconhecimento de padrões. Entretanto, esse tipo de solução é fortemente dependente do treinamento, é computacionalmente custosa e geralmente não é passível de análise teórica de desempenho. Neste trabalho, é proposta a aplicação de algoritmos de registro de imagens para estimar a posição e orientação dos objetos a serem manipulados. Para tanto, propõe-se o uso de um método baseado em Correlação de Fase, de forma a segmentar o objeto de interesse e, simultaneamente, estimar os parâmetros de interesse. Como uma das principais contribuições, são apresentadas considerações sobre o registro de imagens por Correlação de Fase, destacando-se limitações que aparentemente passaram despercebidas pela comunidade científica nos últimos 25 anos. Com base nessas considerações, sob condições de teste de interesse da aplicação e assumindo-se o erro absoluto médio como figura de mérito, o método proposto melhora o desempenho de estimação de movimentos de rotação em mais de 1000% em relação à forma em que o método de Correlação de Fase se apresenta na literatura. [resumo fornecido pelo autor]
Keywords: Registro de imagens; Robótica; Image registration; Robotics